The Role of Public Governance in Environmental Sustainability - Handoyo, Sofik (Jurnal Ilmiah Peuradeun, 2018)
The purpose of the study is to investigate the relationship between public governance and environmental sustainability performance. The public governance in this study refers to indicators namely public accountability, government effectiveness, control of corruption, regulatory quality and political stability and rule of law. Meanwhile, environmental sustainability refers to country’s environmental performance. The study was driven by phenomena that countries located in the same categorization of Geographic but have different environmental sustainability performance. The study involved 178 countries member of World Bank. Purposive sampling technique was used in this study. Public governance and environmental sustainability were treated as two independent variables. The degree of correlation between variables was analyzed using Bivariate correlation analysis. World Governance Index (WGI) was adopted as an approach to Public governance measurement. Environmental Sustainability was measured using Environmental Performance Index (EPI). The findings showed that Public governance indicators namely, public accountability, government effectiveness, rule of law, regulatory quality, control of corruption and political stability have a positive and significant correlation with environmental sustainability performance.